Business partnership, women empowerment and support to women living with HIV/AIDS in Kabale, Uganda - Mwosi, Fabian; Eton, Marus; Aluonzi, Burani; Olupot, Simon Peter; Alia, Richard (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: This investigation stemmed from the need to support women living with HIV/AIDS using community approaches of business partnerships and women empowerment as opposed to government-and private sector-led support. Research Methodology:  This study adopted systematic sampling techniques for data collection from 123 women living with HIV/AIDS from a designated health center in Kabale Municipality. Women taking ARVs were identified from the points where they were collecting their ARVs, and were given questionnaires after consenting to participate in the study. Results: Women empowerment increased decision-making power, while business partnerships decreased dependence on male partners. Women empowerment increases support for women living with HIV/AIDS compared with business partnerships. Business partnerships, as observed in this study, draw weak relationships from many women living with HIV/AIDS. Women empowerment programs that cut across all age groups are effective in supporting vulnerable women living with HIV/AIDS. Limitations: This study encountered the challenge of interfacing with the respondents, since the information was collected by those in charge of the drug distribution center but not the researchers, and these affected in-depth investigations. Women accessing HIV/AIDS do not want to be identified because of stigma within the community. Contributions: From a public health perspective, designers of intervention programs to support women living with HIV/AIDS should consider inclusiveness in design, driven by age categorizations. Designers of intervention programs to support women living with HIV/AIDS should target business partnerships among low-income earners to reduce vulnerability.